Extended spectrum-based pushover analysis for predicting earthquake-induced forces in tall buildings. (15th July 2018) - Liu, Yang; Kuang, J.S.; Huang, Qunxian
Highlights: Most of pushover methods are used for estimating earthquake-induced displacements. Extended spectrum-based pushover analysis (ESPA) procedure is proposed. ESPA is developed for predicting earthquake-induced forces of high-rise buildings. Case study of high-rise buildings to different motion intensities is conducted. Results of ESPA agree very well with those of nonlinear time history analysis. Abstract: Achievements have been made in the development of effective and accurate simplified methods for predicting the seismic demand of tall buildings. However, most of these methods are primarily focused on the estimation of seismic deformation of buildings, while no analysis and calculation of earthquake-induced forces in the structures have been presented. Based on the spectrum-based pushover analysis (SPA) for estimating the seismic demand of tall buildings, where the complicated vibration mode coupling in the nonlinear vibration of structures is simplified, an extended spectrum-based pushover analysis (ESPA) is developed for the fast prediction of earthquake-induced forces of tall buildings. In ESPA, a linear response spectrum analysis procedure is incorporated into SPA to consider the modal combination in the linear stage of vibration. A case study of two high-rise, special steel moment-resisting frame buildings subjected to different levels of ground-motion intensity is conducted to investigate the applicability and accuracy of the ESPA method. Comparisons of the results of earthquake-induced forces are made among ESPA, nonlinear response time history analysis (NLRHA), N2 method, modal pushover analysis (MPA) and consecutive modal pushover analysis (CMP). It is seen that the earthquake-induced forces, including bending moments and shear forces, predicted by the proposed ESPA method agree very well with those of NLRHA.